(untitled) (Baghdad Science Journal, 2025)
Four antimony compounds were used in this inves as additives to retard combustion of unsaturated polyester and epoxy resins, namely: 1. Tetraethyl ammonium tribromoethylantimonates (additive I). 2. Tetraethyl ammonium chlorodibromoethylantimonates (additive II). 3. Tetraethyl ammonium trichloroethylantimonates (additive III). 4. Tetraethyl ammonium bromodichloroethylantimonates (additive IV). The effects of these additives on flammability of unsaturated polyester and epoxy resins have been studied by using sheets of the resins with weight percentages of (0.5,1.0,1.5,2.0,2.5&3.0%) of the additives in dimensions of (150 X150X3)mm .Three standard test methods were used to measure the flame retardation which are: (ASTM:D -2863), (ASTM:D-635)and (ASTM:D-3014). The results obtained from these tests indicated that, additive I has a high efficiency as flame retardant causing , self – extinguishing (S.E.) at the percentage of (2.0%) for unsaturated polyester resin and the percentage (2.5%) for epoxy resin. Self – extinguishing (S.E.) of additives II and IV were at the percentage of (2.5%) for unsaturated polyester resin and (3.0%) in the case of epoxy resin. Additive III showed low effect on flammability in both resins